Antiviral Drugs Used to Treat COVID-19 are not Liver Safe: A Comparative Experimental Study - Asiye Aslı Emniyet Sert; Cemile Merve Seymen; Gülnur Take Kaplanoğlu (Gazi Medical Journal)
Objective: This study aimed to determine whether the medication alone might be effective in the drug-induced liver damage that was reported during coronavirus disease-2019 (COVID-19) in healthy rats. Methods: Thirty-three 8-10 week old Wistar albino male rats were separated into seven groups: the sham control groups for intravenous, subcutaneous, and gavage stress; the acyclovir, hydroxychloroquine, anakinra, and favipiravir groups. At the end of the experimental period, hematoxylin-eosin and silver impregnation histochemical, tumour necrosis factor-alpha (TNF-α)/interleukin-1 beta (IL-1β)/IL-6 immunohistochemical stainings were performed on liver tissue. Data were supported statistically. Results: Morphological degeneration were observed in both the classic liver lobule and portal triad regions with drug administration. The intensity of the reticular fibers was found to be decreasing in the medicament groups, especially around the vena centralis. TNF-α, IL-1β, and IL-6 immunoreactivities were found to be significantly higher in the antiviral drug-administered groups than in the sham control groups. Conclusion: It is concluded that liver damage was reported for treating COVID-19 triggered by the medicines applied.